Public Procurement Nexus Social for Mitigate the Corruption: Lesson from Indonesia - Prakasa, Satria Unggul Wicaksana; Hariri, Achmad; Haq, Hilman Syahrial; Arafah, Adhy Riadhy; Sahid, Muallimin Mochammad (Lex Scientia Law Review, 2023)
This study delves into the vulnerability of Indonesia's National Budget (APBN) to corruption, specifically in the Procurement of Goods and Services, with a particular focus on the potential for misallocation across regions. Building on significant scholarly contributions from both Indonesian and international researchers, the research undertakes a thorough examination of preventive measures against corruption in public procurement. Employing a Participatory Action Research (PAR) approach, the study integrates community solidarity into its corruption prevention model, utilizing a combination of data collection methods such as questionnaires, interviews, and focus group discussions (FGDs). A central topic in the study is the important role of e-procurement in combating corruption, advocating for its transparent and accountable application as a deterrent. To bolster preventive efforts, the research proposes mandatory declarations from tender participants, along with an enhanced auction rebuttal mechanism throughout the various stages of procurement. The preventative framework underscores the significance of civilian, academic, and journalistic supervision to proactively identify corruption and conflicts of interest. Recognizing the nuanced nature of fraud patterns at the provincial level, the study advocates for a region-specific approach to maximize the effectiveness of e-procurement. This regional focus aligns with the study's emphasis on the involvement of relevant agencies operating at the local level. In essence, this research contributes a targeted analysis to complement existing literature, aiming to curb corruption in public procurement through strategic and context-specific preventive measures.